2020
DOI: 10.4317/medoral.23665
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular diseases and apical periodontitis: association not always implies causality

Abstract: Background Several studies published in the last two decades have found an association between the prevalence of apical periodontitis (AP) or root canal treatment (RCT) and cardiovascular diseases (CVDs). However, the demonstration of association does not prove by itself the existence of a cause–effect relationship. Two diseases can appear as statistically related without any of them directly affecting the values of the other, resulting in a non-causal relationship. The aim of this narrative revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…In addition, they agree with the studies that have found a higher prevalence of AP in patients with ACVD [ 25 , 50 , 51 , 52 , 53 , 54 ]. Although few longitudinal studies have been conducted investigating the relationship between AP and cardiovascular events [ 10 ], it has been found that in patients <40 years old, incident of radiolucent periapical lesions was significantly related to the development of coronary heart disease [ 20 ]. Another study showed that acute coronary syndrome is more frequent in subjects with untreated teeth with AP (OR = 2.72; p = 0.022) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, they agree with the studies that have found a higher prevalence of AP in patients with ACVD [ 25 , 50 , 51 , 52 , 53 , 54 ]. Although few longitudinal studies have been conducted investigating the relationship between AP and cardiovascular events [ 10 ], it has been found that in patients <40 years old, incident of radiolucent periapical lesions was significantly related to the development of coronary heart disease [ 20 ]. Another study showed that acute coronary syndrome is more frequent in subjects with untreated teeth with AP (OR = 2.72; p = 0.022) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The weighted average of teeth with AP in adult patients is 5.4%, with 36% of RFT associated with radiolucent periapical lesions [ 6 ], the radiographic sign of AP [ 7 ]. The possible relationship of AP with systemic pathologies has been raised [ 8 ], having found an association with diabetes [ 9 ] and cardiovascular disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, an association between AP and some systemic diseases, such as diabetes mellitus ( 5 ) and cardiovascular disease ( 6 ), has been found. This association would be based on the presence of a pro-inflammatory status, as well as risk factors common to both AP and the systemic disease ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking patients should also know that their prognosis for RCT has lower expectations of success. If, in addition to smoking, patients have other risk factors such as cardiovascular disease [ 44 , 45 ] or diabetes [ 18 , 46 , 47 ], smokers should know that their RFTs have very high likelihood to end up being lost.…”
Section: Discussionmentioning
confidence: 99%